Minimally Invasive Approach to Eliminate Pyogenic Granuloma: A Case Report. (26th January 2012) - Chandrashekar, B.
Abstract : Pyogenic granuloma is one of the inflammatory hyperplasia seen in the oral cavity. The term is a misnomer because it is not related to infection and arises in response to various stimuli such as low-grade local irritation, traumatic injury, or hormonal factors. It is most commonly seen in females in their second decade of life due to vascular effects of hormones. Although excisional surgery is the treatment of choice for it, this paper presents the safest and most minimally invasive procedure for the regression of pyogenic granuloma.